PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMPN 1 TILATANG KAMANG - Virly, Nabila (Departemen Matematika, 2024)
One of the goals of learning mathematics is to improve students' ability to express their mathematical thinking in oral, written and graphic form and to understand mathematical models. However, the level of ability of class IX students at SMPN 1 Tilatang Kamang in this regard is still less than optimal. By using the Quantum Teaching (QT) learning method you can overcome this problem. This research is focused on finding out whether class IX students at SMPN 1 Tilatang Kamang who use the QT method can outperform their friends in conventional mathematics classes. This research uses descriptive and pseudo. Class IX.6 was the experimental class and class IX.4 was the control class in this study, which was selected using a simple random sampling technique. The hypothesis test result of the sample class is 0.024 so is rejected. Based on this, it can be concluded that by using the QT model the ability of class IX students at SMPN 1 Tilatang Kamang in communicating mathematical ideas is better than students with conventional learning.Keywords– Mathematical Communication Skills, Quantum Teaching Learning Model, Conventional Learning